Role of Folate, Cobalamin, and Probiotics in COVID-19 Disease Management [Letter] - Asad D; Shuja SH (Dove Medical Press, 2021)
Dayab Asad,1 Syed Hasan Shuja2 1Jinnah Sindh Medical University, Karachi, Sindh, Pakistan; 2Dow Medical College, Karachi, Sindh, PakistanCorrespondence: Syed Hasan ShujaDow Medical College, Dow University of Health Sciences, Baba-e-Urdu Road, Karachi, 74200, PakistanTel +92 3200250770Email hasanshuja6@gmail.com View the original paper by Dr Yassin and colleagues